Organization-Level Determinants of Women in Management - Blum, Terry C.; Fields, Dail; Goodman, Jodi S. (Academy of Management Journal, 1994)
This study investigated the association of organizational characteristics with the percentage of management positions held by women in a group of medium-sized to large private sector workplaces. Results support hypotheses derived from resource dependence and institutional theories and illustrate that characteristics of organizations predict a substantial portion of the variation in the percentage of management positions filled by women across industries. Effects differ for organizations in manufacturing and nonmanufacturing industries.